The 212 Movement in the Ethical Frame of Emmanuel Levinas (Jurnal Bina Praja, 2019)
Identity politics promoted by the 212 Movement has led to increased intolerance in society. This study captured this problem through the perspective of Emmanuel Levinas’ Ethics.  According to Levinas, the act of intolerance occurs because we see the Other, not with ideas, ideologies, teachings, doctrines, interests, and religion that should be upheld above all things. Our attachment to the ideas we has about others often makes us fail to treat them as humans because we are prevented from encountering them directly. For this reason, this study aims to find out the negative consequences caused by the 212 Movement through the philosophical perspective of Emmanuel Levinas' ethics. With descriptive methods, literature study, and a qualitative approach, the results of the study showed that identity politics carried out by the 212 Movement could not be justified in ethical relations. The 212 Movement saw other human beings as objects that can be used to achieve their personal or group goals. The movement has controlled and exploited their fellow believers, and not reluctant to carry out hateful propaganda to people outside their group. Levinas ethical relations open a new type of relations that are different from idea-based relations. Encountering others makes us realize that they are not merely skin, flesh, and blood that can be destroyed just like that.
Keywords: Intolerance; Ethical Relations; Identity Politics; 212 Movements